Implementasi Manajemen Pendampingan Kelompok Kerja Guru (KKG) dalam Penguatan Guru sebagai Pemimpin Perubahan di Kabupaten Pesawaran - Zulkifli Zulkifli; Tri Yuni Hendrowati; Fatqul Hajar Aswad; Siswoyo Siswoyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the implementation of mentoring management within the Teacher Working Group (KKG) to empower teachers as leaders of change in Pesawaran Regency. The research method used was descriptive research with a qualitative approach. The subjects consisted of the KKG chairperson and teacher members selected through purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through technical triangulation. The results indicate that the implementation of KKG mentoring management was carried out through the stages of planning, organizing, implementing, and evaluating systematically and continuously. Planning was based on an analysis of teacher needs, organizing was supported by a clear structure and division of tasks, implementation used a collaborative approach through workshops, coaching, and discussions on learning practices, while evaluation was conducted through online reflection and follow-up. KKG mentoring has been shown to improve teachers' competence, self-confidence, creativity, and leadership skills as agents of change in the school environment. The program's success was supported by responsive leadership, a collaborative culture, active teacher participation, and facilitator support. Challenges faced included limited time, funding, coverage, and teacher workload. The study concludes that the mentoring management of the Teacher Working Group (KKG) in Pesawaran Regency positively contributed to strengthening teachers as leaders of change through collaborative and ongoing professional development. However, improvements are still needed in aspects such as impact evaluation, structural support, and program sustainability. Keywords: Mentoring Management, Teacher Professionalism, Leaders of Change, Teacher Competency Development